Effect of plant spacing and depth of USG placement on yield of Boro rice - Das, S; Chaki, AK; Sobhan, N; Hossain, MM; Arshad, HM (Bangladesh Agronomy Journal, 2015)
Abstract not available Bangladesh Agron. J. 2014, 17(1): 103-106